Working with Young Children with Special Needs in Earthquake Zone: Experiences of Special Education Teachers - Nisa Demir; Hikmet Taha Acartürk; Funda Ün Yumrutepe; Beyza Elif Çiçen; Emine Ayyıldız (Sakarya University Journal of Education)
Two devastating earthquakes occurred in the southeast of Türkiye on February 6, 2023. Millions of people were damaged in these Kahramanmaraş-centered earthquakes, which seriously affected 11 provinces. It is known that children and individuals with special needs were most affected by such traumatic events, and young children with special needs are in the group at the highest risk in this respect. In this study, in which we employed qualitative phenomenological approach, we aimed to reveal the experiences of special education teachers who worked or are currently working in the earthquake zone with young children with special needs. In this study, we conducted semi-structured interviews with 12 teachers determined by purposeful sampling and we analyzed the data inductively. The findings demonstrate that the participant teachers provided services not only to young children with special needs but also to all children in need. It is also noted that there were deficiencies in planning for working with children with special needs, there were difficulties in initiating and maintaining educational activities, and teachers' experiences of working in the region had positive effects on them. Since the physical and psychological difficulties of the earthquakes and the need for support in the region will continue for a long time, it is essential to provide training on what to do in disasters to teachers who are currently on duty and those who will be assigned later. The necessity of providing psychological support to teachers during active work in the region and upon their return should also be underlined.